Exploiting the potential of plants with crassulacean acid metabolism for bioenergy production on marginal lands. - Borland, A; Griffiths, H; Hartwell, J; Smith, J (2009)
Crassulacean acid metabolism (CAM) is a photosynthetic adaptation that facilitates the uptake of CO(2) at night and thereby optimizes the water-use efficiency of carbon assimilation in plants growing in arid habitats. A number of CAM species have been exploited agronomically in marginal habitats, displaying annual above-ground productivities comparable with those of the most water-use efficient C(3) or C(4) crops but with only 20% of the water required for cultivation. Such attributes highlight the potential of CAM plants for carbon sequestration and as feed stocks for bioenergy production on marginal and degraded lands. This review highlights the metabolic and morphological features of CAM that contribute towards high biomass production in water-limited environments. The temporal separation of carboxylation processes that underpins CAM provides flexibility for modulating carbon gain over the day and night, and poses fundamental questions in terms of circadian control of metabolism, growth, and productivity. The advantages conferred by a high water-storage capacitance, which translate into an ability to buffer fluctuations in environmental water availability, must be traded against diffusive (stomatal plus internal) constraints imposed by succulent CAM tissues on CO(2) supply to the cellular sites of carbon assimilation. The practicalities for maximizing CAM biomass and carbon sequestration need to be informed by underlying molecular, physiological, and ecological processes. Recent progress in developing genetic models for CAM are outlined and discussed in light of the need to achieve a systems-level understanding that spans the molecular controls over the pathway through to the agronomic performance of CAM and provision of ecosystem services on marginal lands.